Modulation of cerebral ketone metabolism following traumatic brain injury in humans - Bernini, Adriano (J Cereb Blood Flow Metab, 2018)
Adaptive metabolic response to injury includes the utilization of alternative energy substrates – such as ketone bodies (KB) – to protect the brain against further damage. Here, we examined cerebral ketone metabolism in patients with traumatic brain injury (TBI; n = 34 subjects) monitored with cerebral microdialysis to measure total brain interstitial tissue KB levels (acetoacetate and β-hydroxybutyrate). Nutrition – from fasting vs. stable nutrition state – was associated with a significant decrease of brain KB (34.7 [10th–90th percentiles 10.7–189] µmol/L vs. 13.1 [6.5–64.3] µmol/L, p < 0.001) and blood KB (668 [168.4–3824.9] vs. 129.4 [82.6–1033.8] µmol/L, p < 0.01). Blood KB correlated with brain KB (Spearman’s rho 0.56, p = 0.0013). Continuous feeding with medium-chain triglycerides-enriched enteral nutrition did not increase blood KB, and provided a modest increase in blood and brain free medium chain fatty acids. Higher brain KB at the acute TBI phase correlated with age and brain lactate, pyruvate and glutamate, but not brain glucose. These novel findings suggest that nutritional ketosis was the main determinant of cerebral KB metabolism following TBI. Age and cerebral metabolic distress contributed to brain KB supporting the hypothesis that ketones might act as alternative energy substrates to glucose. Further studies testing KB supplementation after TBI are warranted.